Dennard Scaling in Optoelectronics: Scientific Challenges and Countermeasures of Micro‐LEDs for Displays. Issue 12 (10th October 2022) - Lu, Boyang; Wang, Lai; Hao, Zhibiao; Luo, Yi; Chen, Chien‐Ju; Wu, Meng‐Chyi; Tang, Jianshi; Kim, Jong Kyu; Schubert, E. Fred
Abstract: Scaling‐down is the most significant technical strategy to improve performance for microelectronic devices, which is first performed systematically by Robert H. Dennard for silicon integrated circuits. Its main idea is that device parameters such as doping and junction depth must be adjusted when shrinking the dimensions of a field‐effect transistor so that the power density can remain unchanged. Recently, miniaturization of light‐emitting diodes or "microscale light‐emitting diodes (Micro‐LEDs)" is gaining much attention because of their potential for superior display technologies. However, the scaling‐down of LEDs used for solid‐state lighting (SSL) results in extremely low efficiency devices, with the reasons and underlying device physics still unclear. Here the law of Micro‐LED scaling is proposed in analogy to Dennard scaling, through which new perspectives are provided to comprehensively understand the root cause of Micro‐LED inefficiency and the scientific challenges to be addressed for mass commercialization, including subthreshold radiation, size‐dependent effect, and the enhancement of carrier recombination at low current density. Abstract : Microscale light‐emitting diodes (Micro‐LEDs) are considered as a promising display technique, but its miniaturizationsuffers from significant inefficiency. This paper discusses the underlying physical mechanisms of inefficiency and possible solutions to address them from the perspective of the law of scaling down, which provides a guideline to understand the physical processes and optimize the device performance.